(NsO^INENIQ(B: (NpXESY (B[1889-1891] ; [1895- 1904] /s (N~ASTX (B12, (N~ASTX (B13s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1978)
(Nw (B12-13 (NTOMAH SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI PXESY(B, (NNAPISANNYE (B1889-1891 (NI (B1895-1904 (NGG(B.s
rus
Keywords: (NpXESYs